2017
DOI: 10.18632/oncotarget.19843
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and brain tumor: a systematic review and meta-analysis

Abstract: BackgroundPatients with brain tumor are in risk of depression or depressive symptoms, but the estimated prevalence varies between studies. The aim of this study is to get a proper summarized estimate of depression prevalence in brain tumor patients.MethodsLiterature search on Pubmed, PsycINFO, and Cochrane library from January 1981 through October 2016. The prevalence of depression or depressive symptoms in brain tumor patients was estimated by screening scales and analyzed using stratified meta-analysis and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 79 publications
3
43
2
Order By: Relevance
“…17 Depression was prevalent among patients with brain tumour around the time of diagnosis or treatment. 18 The prevalence of depression among primary brain tumour patients has been reported to be 2.5% to 15.4%, 12 and as much as 44% among all brain tumour patients. 19 A study in Taiwan found that the prevalence of depression among patients with cancer was 20%.…”
Section: Discussionmentioning
confidence: 99%
“…17 Depression was prevalent among patients with brain tumour around the time of diagnosis or treatment. 18 The prevalence of depression among primary brain tumour patients has been reported to be 2.5% to 15.4%, 12 and as much as 44% among all brain tumour patients. 19 A study in Taiwan found that the prevalence of depression among patients with cancer was 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric disorders, such as schizophrenia, bipolar disorder, and depression, are extremely heritable complex polygenetic neurodevelopmental disorders ( 1 , 35 38 ). Despite the large market for new psychiatric drug therapies that already exist, the drug discovery for treating psychiatric disorders is stagnant ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 Additionally, the high intercorrelation between fatigue and depression in our findings suggests that interventions to reduce symptoms of depression may be also beneficial. Depression is prevalent in approximately 22% of brain tumor survivors 32 and is associated with cognitive impairment and other health risks (eg, overall survival and suicide risk). 33 However, it should be noted that median levels of depression in our sample were in the minimal/no depression to mild range and that the clinical cutoff for depression (PHQ ≥ 10) did not significantly differ between groups.…”
Section: Median T-scores [Iqr]mentioning
confidence: 99%